The re-appropriation of ideational meanings through drawings: A case of 5-year-old child experience in learning to mean - Gunawan, Wawan (Universitas Pendidikan Indonesia, 2018)
During the last decades, how children make meaning of particular worlds (e.g., events) through drawings has been well-documented. To add to this growing body of research, the present study attempts to document 5-year-old child experience in exploring ideational meanings represented in drawings as part of her home literacy practices in a transition into a dominant English school discourse in a multilingual context of the United States. Empirical data were garnered from the child’s drawings made at home, informal interviews with the child, and observation field notes focusing on the child’s think-aloud practices of drawing along with the features of the drawings in comparison with the captured movie images. These data were discursively analyzed using the concept of ideational meanings anchored in systemic functional and multimodal discourse approaches to capture the expansion of ideational meanings manifested in the child’s drawings. The semiotic analysis reveals that the child re-appropriated her drawings as a multi-semiotic resource to extend her understanding of the subject matter gained from the movie series. The ideational meanings were made subjectively through the interpretation of the drawings which have meaning potentials leading to the construction of meta-knowledge. The practical implication of this study is that language teachers may make use of drawings as a multi-semiotic resource for scaffolding young learners in learning second and foreign languages (e.g., English).